ANALISIS BENTUK MUSIK SIKE GARAPAN SANGGAR MELATI DESA KEMANTAN KEBALAI KABUPATEN KERINCI - Elvin Martius; Esy Maestro; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract The research aimed at analyzing Sike musical form arranged by Sanggar Melati. The design of the research was qualitative using content analysis. The findings showed the Assale and Aiyala song arranged and managed by Sanggar Melati appeared within one part. The pattern of the song were managed using stepped and jumped interval. The antecedent phrase was feminine beginning and masculine ending. The melody was played in D minor 4/4. The rhythm pattern of rebana, both of the songs were similar in their musical principles. Keywords : analisis bentuk musik, sike